DISKRIPSI HUBUNGAN KEPRIBADIAN, EMOSI DAN PERILAKU ‘ORIENTASI SERVICE’ GURU DI ERA INDUSTRI 4.0 - Alwi, Muhammad; Wiyono, Bambang Wahyu; Bafadhal, Ibrahim; Imron, Ali (JURNAL AL-TANZIM, 2019)
The purpose of this study was to find out how the Personality Profile (Big Five), Emotional Intelligence (EI) and 'Orientation Service' Behavior (Organizational Citizenship Behavior, OCB) were high school teachers in Pasuruan Regency. This study is a descriptive-quantitative study. Data obtained from 175 respondents with cluster method, random random. The results showed that the respondents had a relatively young age (average under 40 years), with the proportion of men and women almost the same, and having a Big Five quite high (with Mean, 107, 76), Emotional Intelligence that was quite High (with Mean, 81.74) and also High OCB (with Mean, 71.39). These results are expected to have an impact on positive personality and Emotional intelligence will have a fairly good effect on organizational life and service-oriented behavior where it is all expected in educational institutions. This profile provides a preliminary description that teachers in Pasuruan Regency have readiness to welcome the changes needed for success in the era of 4.0